Covid-19 effects on students' teaching and learning perspectives in Malaysian varsities - Zambri, Harun; Firdaus, Mohamad Hamzah; Shuhaimi, Mansor; Abdus Samad, Mahmud; Hashimah, Hashim; Mohamed Thariq, Hameed Sultan; N. M. Zuki, N. M.; Mohd Danial, Ibrahim; Hasril, Hasini; Mohd Rashdan, Saad; Ahmad Rasdan, Ismail (Universiti Putra Malaysia, 2021)
The COVID-19 pandemic has had dramatic effects on the socio-economic and well beings of Malaysians. The objective of the study is to find the effects of the pandemic on university students both on the technical side, such as the sufficiency of infrastructure and the internet to support online teaching and learning (T&L), as well as on the social side, such as stress level and focus on the study. The nationwide study on the effect of the pandemic on Malaysian varsities students was conducted at the end of 2020. There are many important issues uncovered in this study ranging from the technical side, such as internet-ready programs, socio-economic side, to the psychological perspectives. It shall provide invaluable insights to the related ministries while preparing appropriate reactions during the recovery period. The survey revealed that almost 74% of students highlighted that internet coverage and connectivity was the main issue in online T&L. Although statistics show that 90% of Malaysian households have access to the internet, 49% of students reported that their internet connections were poor. The effects of the pandemic are far-reaching, students belonging to the most vulnerable category find themselves in the most non-conducive place to learn, and they are disturbed by siblings. The socio-economics impacts brought about by the pandemic cause ripple effects onto their families. The government distribution of relief aids has lessened the burden of many people, including students; nevertheless, much improvement could be made, especially in the internet facility and coverage.